The importance of programming paradigms to manufacturing engineering graduates: A case study from international Islamic university Malaysia graduates University Malaysia Graduates - Fauri @ Fauzi, Muhammad Ashraf; Husin, Hafiz; Zuhud, Daeng Ahmad Zuhri (Trans Tech Publications Ltd., Switzerland, 2014)
Digital computers that automate manufacturing process are an important aspect for any manufacturing engineers in the modern world. Selection of the programming paradigm (PP), as well as the programming language (PL) that supports it, is crucial to ensure the correct ideas are being used to automate the solution of the problem. In current Malaysian Higher institution practices, various PPs and PLs courses are offered to current undergraduate manufacturing majors. An online survey was deployed to experienced manufacturing engineers from various manufacturing specializations in the industry. Graduates from one of Malaysia’s public universities, International Islamic University Malaysia (IIUM) have been chosen for this particular study. From the survey, it has been found that almost 80% of the participants agreed that PPs are important for manufacturing graduates. It was found out that 90% of the participants were from intermediate (scale of 3) until poor (scale of 1) to express their ability to explain PPs if asked. Only about 10% are able to explain on PPs (scale of 4 and 5). The study concluded that majority of the manufacturing graduates from IIUM agreed that PP is an important subject to be taught in university. However, it was found the majority of the manufacturing graduates lack the knowledge and understanding of PPs and general PLs.